2020
DOI: 10.1016/j.heliyon.2020.e03761
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin and metformin on development of pentylenetetrazole-induced seizure in mice

Abstract: Recent studies have shown that statins and Metformin may have beneficial effects on seizure through different mechanisms. In the current study, we investigated whether Metformin, Atorvastatin, and concomitant uses of them have beneficial effects on pentylenetetrazole (PTZ)-induced kindling. Adult male C57BL/6 mice were randomly divided into four experimental groups with seven mice in each group. Group 1, control group; group 2, received Metformin (200 mg/kg, i.p); group 3, received Atorvastatin (10 mg/kg, i.p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Treating rats with pilocarpine hydrochloride-induced epilepsy for 5 days with metformin decreased levels of p-mTOR protein and elevated levels of p-AMPK protein along with having anti-epileptic and anti-convulsant effects [ 106 ]. It has recently been suggested that mTOR regulation of autophagy may be responsible for the anti-convulsant effects [ 107 ]. Metformin treatment also suppressed expression of BDNF and its receptor, trk B, which are hyper-expressed in the epileptic brain and represent a pathological signaling cascade in mesial temporal lobe epilepsy [ 106 , 108 ].…”
Section: Rationale For Using Metformin To Treat Neurological Disordersmentioning
confidence: 99%
“…Treating rats with pilocarpine hydrochloride-induced epilepsy for 5 days with metformin decreased levels of p-mTOR protein and elevated levels of p-AMPK protein along with having anti-epileptic and anti-convulsant effects [ 106 ]. It has recently been suggested that mTOR regulation of autophagy may be responsible for the anti-convulsant effects [ 107 ]. Metformin treatment also suppressed expression of BDNF and its receptor, trk B, which are hyper-expressed in the epileptic brain and represent a pathological signaling cascade in mesial temporal lobe epilepsy [ 106 , 108 ].…”
Section: Rationale For Using Metformin To Treat Neurological Disordersmentioning
confidence: 99%
“…Recently, it has been described that metformin reduces CHOP expression and apoptosis induced by status epilepticus in rats [68]. The beneficial effects of metformin on this model could also be due to an improvement in autophagy [69]. Additional reports indicate that AMPK activation by metformin decreases seizure susceptibility, facilitates seizure termination, and reduces the number and duration of seizures in a PTZ-induced epilepsy model [70].…”
Section: Epilepsymentioning
confidence: 97%
“…and intraperitoneal (i.p.) injection of PTZ models in our current work, which have been utilized widely as the lab assessments to evaluate the anti-seizure effects of medication and to develop new antiepileptic therapies [ 40 , 41 , 42 , 43 , 44 ]. Similarly, the maximal electroshock-induced tonic-clonic seizure is the most severe electroshock convulsive response induced by supramaximal electrical stimulation currents.…”
Section: Introductionmentioning
confidence: 99%